Two new species of the whip-spider genus Heterophrynus (Arachnida: Amblypygi) with complementary information of four species - Chirivi-Joya, Daniel; Moreno-González, Jairo A.; Fagua, Giovanny (Zootaxa, 2020)
The family Phrynidae has been mainly recorded from America, including the Antilles, and Heterophrynus is one of its genera endemic of South America and is mainly associated with Amazonian ecosystems. Currently, the genus has 16 valid species, but many original descriptions are ambiguous or incomplete. The more complete work about this genus only includes seven of the currently valid species, and in some cases, some characters useful for the species identification, were not described. This situation hampers the species recognition and the comparison among species to propose diagnosis accurate. Using characters from the male and female genitalia to improve the diagnosis, we present complementary descriptions for four species of Heterophrynus and describe two new species. We present details of morphologic variation, compare the pedipalp spines among the species, present actualized distributions, and for first time, we present a complete illustration of the male genital of eight species using SEM pictures.